Clinical Characteristics and Risk Factors for Severe Immune-Related Liver Injury Following Nivolumab and Ipilimumab Combination Therapy - Yuichi Yamazaki; Satoru Kakizaki; Yuki Tamura; Yumeo Tateyama; Tatsuma Murakami; Takuya Adachi; Hiroki Tojima; Toshio Uraoka (Antibodies, 2026)
Background: Combination therapy with nivolumab and ipilimumab (Nivo-Ipi) has substantially improved outcomes in several advanced malignancies but is frequently associated with early-onset, severe immune-related liver injury (irAE-LI). This study aimed to identify pretreatment predictors of severe irAE-LI and to characterize its clinical course. Methods: We retrospectively analyzed 81 patients who received Nivo-Ipi combination therapy between 2018 and 2025. Severe irAE-LI was defined as liver injury requiring systemic corticosteroid therapy. Results: Severe irAE-LI developed in 11 patients (13.6%), with a median onset of 38 days after treatment initiation. More than half of the cases occurred after the first treatment cycle. This exploratory multivariable analysis identified baseline serum Krebs von den Lungen-6 (KL-6) levels of ≥400 U/mL as a potential biomarker associated with a strong preliminary risk signal for severe irAE-LI (odds ratio, 12.60; 95% confidence interval, 2.32–68.60; p = 0.003), whereas conventional liver function tests and inflammatory markers showed no significant association. The robustness of this signal was further confirmed by a sensitivity analysis excluding patients with lung adenocarcinoma (odds ratio 13.21, p = 0.005). Clinically, 54.5% of affected patients experienced steroid-refractory disease or relapse during corticosteroid tapering despite guideline-recommended high-dose corticosteroid therapy. Cytomegalovirus (CMV) reactivation was detected in 50.0% of patients tested on the basis of clinical indicators such as cytopenia or gastrointestinal symptoms, which may have contributed to a pseudo-refractory clinical course in some cases. Conclusions: Pretreatment KL-6 measurement may facilitate risk stratification before Nivo-Ipi therapy. In patients with steroid-refractory or relapsing severe irAE-LI, early introduction of mycophenolate mofetil together with CMV screening may improve clinical management.